On nonlinear dynamic system arising in Potts model - Ganikhodjaev, Nasir; Nawi, Mohamad Ashraf (2009)
From three-state Potts model we produce the recursion relations that provide us numerically exact phase diagrams of the Potts model. Each phase is characterized by a particular attractor and the phase diagram is obtained by following the evolution and detecting the qualitative changements of these attractors. These changements can either be continuous or abrupt, respectively, characterizing second or first order transitions. We present a few typical attractors.